On I-Rigid and q-Rigid Rings - Artemovich, O. D. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We describe q-rigid rings that have no simple noncommutative homomorphic images, and I-rigid rings with periodic and mixed additive groups.